EFFECT OF PRECIPITATION AND CONTAMINATION ORIGIN ON THE EFFICIENCY OF PINACOLYL ALCOHOL IDENTIFICATION IN CONCRETE DEBRIS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Chemical warfare agents (CWAs) pose a significant threat to people and the environment. Nowadays, the war fights take place mostly in urban areas. Here, chemical weapons contaminate materials of different properties, and the behavior of the parent contaminant may vary. Concrete has an alkaline pH and rapidly decomposes chemical warfare agents. The study deals with the analysis of potentially contaminated concrete samples taken from the site of the alleged use of nerve CWA soman (GD, pinacolyl methylphosphonofluoridate) using gas chromatography. The final degradation product of soman alkaline hydrolysis – pinacolyl alcohol (3,3-dimethylbutan-2-ol) – was chosen as the analyte. The method for the preparation of the concrete samples included organic solvent extraction of the contaminant, in which two organic solvents with different polarity, namely acetone and ethyl acetate, were used separately for comparison. The applicability of the method; the extraction efficiency from concrete debris at given time intervals from the time of contamination to the start of extraction; the effect of moisture addition before and after contamination; and the effect of the extractant used were studied. The possibilities of wipe sampling of the concrete surface in case of point and area contamination with pinacolyl alcohol were also monitored. The precision of the quantitative analysis was expressed by measuring the standard deviation and was worse in the case of ethyl acetate. The highest recovery values were observed with extraction from dry concrete, followed by concrete moistened after contamination. In the case of area contamination, a lower efficiency of surface wipe sampling was found. The results are particularly useful in the field analysis of samples after the use of chemical weapons.